The Effect of Environmental Performance and Audit Quality on Carbon Emissions Disclosure in Indonesian Energy Companies - Risma Amalia; Aurellia Faiza Athifa; Agus Triyani (Universitas Islam Sultan Agung, Faculty of Economic and Business, Accounting Dept, 2026)
Abstract This study was conducted in response to growing demands for transparency from companies in the energy sector regarding the disclosure of carbon emissions as a form of environmental responsibility.The study aims to examine the influence of environmental performance and audit quality on carbon emissions disclosure among energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The method used is a quantitative approach with secondary data in the form of annual reports and sustainability reports. The research sample was determined using purposive sampling, comprising 75 observations, with data analysis employing multiple linear regression. The results indicate that, when considered individually, environmental performance does not have a significant effect on carbon emissions disclosure, whereas audit quality was found to have a positive and significant effect. This study contributes to the development of environmental accounting literature and underscores the importance of audit quality in enhancing the transparency of carbon emissions reporting, while also serving as input for companies and regulators in promoting more accountable reporting practices.Keywords: Carbon Emission Disclosure, Environmental Performance, Audit Quality